Doświadczenia nauczycieli w zakresie wspierania motywacji do uczenia się w ujęciu teorii autodeterminacji - Marta Makarewicz (Problemy Wczesnej Edukacji)
The article presents qualitative research in the field of students’ motivation to learn. The aim of the research was to identify and describe ways to support students’ motivation to learn from the perspective of teachers’ experiences in terms of the self-determination theory. Based on the interviews with teachers, the research results were presented taking into account the ways of supporting the need for relatedness, competence and autonomy. The results of the research show a multitude of ways to motivate students. According to the respondents, students’ motivation to learn is largely based on the child’s qualitative relationship with adults and peers.